Effect of different tillage and residue management practices on crop and water productivity and economics in maize (Zea mays) based rotations - Parihar, Muli D.; Parihar, Chiter Mal; Nanwal, Rajendra K; Singh, Aditya K.; Jat, Shankar Lal; Nayak, Harisankar; Ghasal, Prakash C; Jewlia, Hem R; Choudhary, Mukesh; Jat, Mangi Lal (Indian Council of Agricultural Research, 2019)
In recent years, increasing water and labor scarcity & production cost, decreasing farm profitability and climatechange- induced variability are major challenges faced by the farmers of Indo-Gangetic Plains (IGP) in South Asia. Conservation agriculture (CA) based best-bet crop management practices may increase crop productivity, profitability and conserve the natural resources. In a 2-year (2012-2014) study, we assessed the effects of six combinations of tillage and crop establishment (TCE) and residue management options on crop & water productivity, profitability and soil thermal and moisture regimes in maize (Zea mays)-wheat (Triticum aestivum L.) (MW) and maize-chickpea (Cicer arietinum L.) (MC) rotations in Western IGP of India. The treatments consisted of both crops sown on permanent raised beds with residue (PB+R) and without residue (PB-R); zero tilled flat with residue (ZT+R) and without residue (ZT-R) and conventional tilled flat with residue (CT+R) and without residue (CT-R). Overall, 2-year mean maize, wheat and chickpea grain/seed yield was found to be 17.0-23.2, 20.8-24.8 and 22-31.7% higher under CA-based PB+R/ZT+R than CT-R, but it was 5.3-10.9, 4.9-8.4 and 13.8-22.8% higher than CT+R, respectively. The yield of maize, wheat and chickpea was significantly (P<0.05) higher in CA-based PB+R and ZT+R systems compared to CT-R right from first year onwards. The MW and MC, 2-year mean system productivity (based on maize equivalent yield- MEY) was higher by 21.1-21.9 and 18.7-27.5% in CA-based systems (PB+R & ZT+R) than in the CT-R, respectively. CA-based PB+R and ZT+R practices reduced the total system water use in MW and MC rotations by 75-112 mm and 55-90 mm and resulted enhanced system water productivity (WP) compared to CT-R system. Irrespective of crop rotations and TCE practices residue management treatments enhances the soil moisture (in the range of 14.5 to 30.4% during winter and monsoon seasons) and also moderates the soil temperatures. Economic profit for MW and MC rotations was always significantly (P<0.05) higher (168-445 and 215-619 US$/ha/year) in CA-based systems than in CT-R. Findings of our study shows that MW and MC rotations under CA-based system is one of the way for improving crop productivity, WP and farm income with less risk of extreme temperature and moisture stress while sustaining the natural resources in Western IGP of India and other similar agro-ecologies of South Asia.